(untitled) (Proceedings of International Educators Conference, 2024)
In the dynamic landscape of education, the development of linguistic competence among faculty is essential for effective communication, teaching, and professional growth, especially in specialized areas such as English in Engineering. In this context, the didactic opportunities offered by digital learning resources play an important role in improving teachers’ language knowledge, pedagogical skills, and general educational effectiveness. Digital learning resources can meet the specific needs of engineering teachers. provides a variety of interactive language learning platforms. These platforms offer engaging activities, interactive exercises and multimedia content designed to improve vocabulary retention, grammar accuracy and communication skills in technical contexts. Teachers can use these resources to improve their linguistic competence through self-paced learning modules, real-time feedback mechanisms, and personalized learning plans tailored to their skill levels the availability of specific reflective content and authentic materials.[5]